2017
DOI: 10.1111/aji.12797
|View full text |Cite
|
Sign up to set email alerts
|

Paternal HLA‐C is a risk factor in unexplained recurrent miscarriage

Abstract: The results show that HLA-C incompatibility between couples is significantly associated with unexplained recurrent miscarriage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 40 publications
(43 reference statements)
0
10
1
Order By: Relevance
“…Moreover, both CD69 and CD103, that can prevent cell egress and are expressed at a higher level by mucosal memory T cells than circulating memory T cells ( 44 , 46 , 47 ), were observed to be upregulated in human dCD8 cells (Figure 3 ; Figures S6 and S7 in Supplementary Material), indicating that these cells have a “tissue-resident effector-memory T cell” (T REM ) phenotype during human early pregnancy. Although memory dCD8 T cells were hypothesized to be virus-specific T cells to protect the fetus against invading pathogens in uncomplicated pregnancy ( 48 ), the definite role and specificity of these dCD8 T REM cells remain largely unknown and need to be determined by more experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, both CD69 and CD103, that can prevent cell egress and are expressed at a higher level by mucosal memory T cells than circulating memory T cells ( 44 , 46 , 47 ), were observed to be upregulated in human dCD8 cells (Figure 3 ; Figures S6 and S7 in Supplementary Material), indicating that these cells have a “tissue-resident effector-memory T cell” (T REM ) phenotype during human early pregnancy. Although memory dCD8 T cells were hypothesized to be virus-specific T cells to protect the fetus against invading pathogens in uncomplicated pregnancy ( 48 ), the definite role and specificity of these dCD8 T REM cells remain largely unknown and need to be determined by more experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it seems that HLA-G contributes to fetal tolerance by modulating decidual NK cell and APC responses (LeMaoult et al., 2004). Such nonclassical MHC molecules are of key importance not only in the establishment of the pregnancy but also in its maintenance, as revealed by studies in both healthy and pathological pregnancies (Tripathi et al., 2006; Michita et al., 2016; Persson et al., 2017; Meuleman et al., 2018). Notably, it has been shown that immunomodulatory molecules from the B7 family and the soluble HLA-G isoform HLA-G5 are secreted from the placenta during the first trimester and at term via exosomes (Kshirsagar et al., 2012).…”
Section: Main Textmentioning
confidence: 99%
“…And in early pregnancy they are also associated with lower chance of a live birth in women with RM . For example, HLA‐C‐specific antibodies were found more often in women with RM and the reason maybe that they induce platelet activation by placental thromboxane production . Taken together, whether the anti‐HLA antibodies are unrelated or harmful to pregnancy maintenance is still debatable.…”
Section: Antipaternal (Anti‐hla) Antibodiesmentioning
confidence: 99%